Optimization of Secure Data for Steganography and Digital Watermarking Scheme - Rai, Avinash; Todkar, Vivek (International Journal of Computer Sciences and Engineering, 2019)
“Steganography” is a technique that thwarts unauthorized users to have access to the crucial data, to invisibility and payload capacity using the different technique like discrete cosine transform (DCT) and discrete wavelet transform (DWT).The available methods till date result in good robustness but they are not independent of file format. The aim of this research work is to develop a independent of file format and secure hiding data scheme. The independent of file format and secure hiding data scheme in increased by combining DWT and least significant bits (LSB) technique. Accordingly an efficient scheme is developed here that are having better MSE and PSNR against different characters.